The guardians - Christopher, John. (New York : Maxwell Macmillan International, 1992)
In the divided England of the distant future, a recently-orphaned boy flees the sprawling area known as the Conurb for the serene world of the County where the people seem to live a simpler existence.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.0
Young Adult
Keywords: Science fiction; Science fiction